Utilization of Inulin from Mangrove Apple and Pineapple Juice as Prebiotic Drink to Recovery Covid-19 Patients - Pramono, Yoyok Budi; Mulyani, Sri; M. Legowo, Anang; Al-Baarri, Ahmad Ni’matullah; Maula Bernadine, Nathania; Olivia Afri Kusuma, Daniella; Gangsar Listya, Angelique (International Journal of Scientific Research and Management (IJSRM), 2024)
Amidst the COVID-19 pandemic, some individuals have turned to functional foods in an effort to bolster their immune systems. One such functional option is prebiotic drinks. These beverages are crafted from fermented sugars, which serve as a carbon source for lactic acid bacteria. To enhance their functional properties, prebiotic drinks often incorporate inulin—a type of prebiotic. Traditionally, these drinks are milk-based, but for those who cannot tolerate dairy, alternatives have emerged. For instance, pineapple-based prebiotic drinks enriched with inulin from mangrove apples have gained popularity. The process involves extracting inulin from mangrove apples and combining it with pineapple to create a probiotic drink. The resulting beverage derives its sweetness from the natural sugars found in pineapples and mangrove apples. Pineapple contains approximately 2.32% glucose, 1.42% fructose, and 7.89% sucrose, while mangrove apples boast 5.08% inulin, 9.67% soluble dietary fiber, and 0.66% FOS. These sugars serve as nourishment for lactic acid bacteria, ultimately stimulating the production of IgG and IgM antibodies. In summary, the combination of inulin-rich mangrove apples and pineapple’s total soluble solids can contribute to fortifying the body’s immune system during the COVID-19 pandemic.